Surgical Outcomes in the Era of COVID-19: A Stratified Analysis Based on Infection Chronology - Dmytro M. Kosovan (Ukrainian Journal of Cardiovascular Surgery, 2025)
Aim. To investigate the impact of COVID-19 infection timing on postoperative outcomes in patients undergoing surgical treatment for acquired valvular heart disease.Materials and Methods. This single-center retrospective study included 96 patients with confirmed COVID-19 who underwent valvular heart surgery. Patients were stratified into two groups based on the timing of SARS-CoV-2 infection: those infected prior to hospital admission (preoperative COVID-19; n=69) and those infected during hospitalization after surgery (postoperative/hospital-acquired COVID-19; n=27). Clinical, laboratory, and perioperative data were analyzed, including length of hospitalization and ICU stay, duration of mechanical ventilation, use of inotropes/vasopressors, and mortality. Statistical analyses included t-tests, Mann–Whitney U tests, Pearson’s correlation, and chi-square tests.Results. Postoperative COVID-19 infection was associated with significantly worse outcomes, including longer hospital and ICU stays, prolonged mechanical ventilation (169.7 ± 140.8 h vs. 18.1 ± 35.3 h; p<0.001), increased need for inotropic and vasopressor support (dobutamine use: r=0.84; norepinephrine use: r=0.76), and higher mortality. Laboratory findings revealed more profound thrombocytopenia, hyperglycemia, and renal dysfunction in the postoperative group. In contrast, patients with preoperative COVID-19 demonstrated more favorable outcomes, provided that a sufficient interval (≥6–7 weeks) had elapsed between infection and surgery. Strong correlations were observed between mortality and indicators of multiorgan dysfunction, particularly respiratory failure, cardiac decompensation, and pneumonia.Conclusions. The timing of COVID-19 infection is a critical determinant of postoperative prognosis in patients undergoing valvular surgery. Hospital-acquired infection is an independent predictor of adverse outcomes. Elective surgery should be deferred for at least 6–7 weeks after COVID-19 recovery, with individualized risk assessment. Preventing early nosocomial infection in the postoperative period is essential to reduce mortality in cardiac surgery patients.